2021
DOI: 10.1002/asl.1071
|View full text |Cite
|
Sign up to set email alerts
|

Statistical linkage between coastal El Niño–Southern Oscillation and tropical cyclone formation over the western North Pacific

Abstract: This study investigates the modulation of tropical cyclone (TC) formation over the western North Pacific (WNP) by coastal El Niño–Southern Oscillation (ENSO). There is a significant inverse relationship between WNP TC frequency during July–October from 1961 to 2019 and simultaneous Niño 1+2 sea surface temperature anomalies. TC formation is significantly suppressed and enhanced over the subtropical and equatorial WNP during coastal El Niño, respectively, while TC formation exhibits opposite‐signed anomalies du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Previous studies have shown that locations of the maximum SST anomalies related to ENSO can modulate the ENSO impacts on the WNP TC activity (Chen and Tam, 2010;Zhang et al, 2012;Patricola et al, 2016;Zhao and Wang, 2018). Although both the eastern Pacific El Niño (EPE) and central Pacific El Niño (CPE) can cause the dipole anomalies in the WNP TC genesis, the horizontal location of the dipole related to the CPE is more westward compared to the EPE due to the more westward anomalous warming of CPE (Kim et al, 2011;Song et al, 2021). However, the models in HighResMIP-PRIMAVERA project have poor performance in the diversity of El Niño events, there are few differences in the simulation of WNPTCs activity between different El Niño events.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that locations of the maximum SST anomalies related to ENSO can modulate the ENSO impacts on the WNP TC activity (Chen and Tam, 2010;Zhang et al, 2012;Patricola et al, 2016;Zhao and Wang, 2018). Although both the eastern Pacific El Niño (EPE) and central Pacific El Niño (CPE) can cause the dipole anomalies in the WNP TC genesis, the horizontal location of the dipole related to the CPE is more westward compared to the EPE due to the more westward anomalous warming of CPE (Kim et al, 2011;Song et al, 2021). However, the models in HighResMIP-PRIMAVERA project have poor performance in the diversity of El Niño events, there are few differences in the simulation of WNPTCs activity between different El Niño events.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In this study, we focus on the WNPTC genesis during July-October (JASO) that counts more than 60% of the annual WNPTCs (Song et al, 2021). The annual-mean TC genesis both in the observations and models are first binned in 5 °× 5 °grid boxes and then applied the nine-point smoothing (Camargo and Sobel, 2005;Zhang et al, 2016a;Kossin et al, 2016;Tan et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…For an easy comparison of anomalous fields between the HR and LR models, the monthly outputs are commonly interpolated into the 1°×1° gird in advance. In this study, we focus on the WNPTC genesis and track during July-October (JASO) that counts more than 60% of the annual WNPTCs (Song et al 2021). The annual-mean TC genesis and track both in the observations and models are first binned in 5°×5° grid boxes and then applied the nine-point smoothing (Camargo and Sobel 2005;Kossin et al 2016;Zhang et al 2016a;Tan et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, typhoon activity cannot be forecasted directly by ENSO intensity. In fact, during 1961-2019, the overall direct correlation between the typhoon frequency in the WNP and the SST anomaly during the typhoon season was only −0.14 (Song et al, 2022). The reason lies in the diverse effects of ENSO on typhoons (Shi et al, 2019;Guo and Tan, 2021).…”
Section: Introductionmentioning
confidence: 98%